National market of diagnostic tests and test systems - T. S. Brytanova; A. V. Samko; Ye. H. Knysh (Zaporozhye State Medical University, 2020)
The aim of the work was to analyze the market of diagnostic tests and test systems that are in circulation in Ukraine. Materials and methods. To achieve this goal, electronic and paper official sources of information were used, as well as pharmacy websites. The search, analytical, systematic, comparative and statistical methods and methods of mathematical and logical analysis were used in the work. Results. Analysis of the modern market of diagnostic tests and test systems were allowed to establish the range and brand structure (90 manufacturers). The vast majority of them are outside Ukraine (85.5 %). Among foreign producers, the largest importer is China (19.5 %). In the course of work to determine the level of competition between manufacturers of similar groups of tests and test systems set the coefficient of tension. To determine the level of availability, price liquidity and solvency adequacy ratios were calculated. Conclusion. The Ukrainian market of diagnostic tests and test systems was studied. It was established that the company structure consists of 90 manufacturers and 20 countries. The vast majority of products come from importing countries (85.5 %), where the leader is China (19.5 %). Analysis of competitiveness showed that the greatest competition was observed among companies that produce tests to determine pregnancy, glucose, ketones, nitrites and protein in the blood and urine (Kvi = 0.96), and there was no test manufacturers for sperm testing (Kvi = 0). The calculated price liquidity and adequacy of solvency ratios indicate high price competition and low availability for some groups of diagnostic tests and test systems.